ENHANCING DIGITAL CONTENT DESIGN LITERACY THROUGH CANVA TRAINING FOR PARTICIPANTS IN THE 2026 PHASE 2 NATIONAL COMMUNITY SERVICE PROGRAM - Ferdinandus Lidang Witi; Yosep Thobias Parera; Maria Adelvin Londa (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2026)
Digital transformation demands that the younger generation develop the ability to create creative and communicative digital content. One important skill to develop is digital content design with the easily accessible, user-friendly Canva platform. The 2026 National Community Service Phase 2, themed "Becoming a Digital Content Design Expert with Canva for High School Students," aims to improve participants' understanding and skills in digital content design. The activity was held online on May 16 and 23, 2026, through a collaboration between various universities and organizations in Indonesia. The implementation method included preparation, implementation, and evaluation stages. Learning was conducted through webinars, demonstrations, hands-on practice, interactive discussions, and questions and answers. The evaluation used pre-test and post-test instruments with a Likert scale of 1–5, attended by 344 participants in the pre-test and 277 participants in the post-test. The evaluation results showed an increase in the average score from 3.44 to 3.74, an increase of 8.72%. The highest increase occurred in the indicator of understanding visual design concepts, from 3.15 to 3.63. Furthermore, the understanding of information layout increased from 3.15 to 3.56, and the understanding of Canva usage increased from 3.89 to 4.06. These results indicate that the training was effective in improving participants' digital literacy, creativity, and visual communication skills. Participant responses also demonstrated high interest in developing advanced digital competencies, particularly Canva's integration with Artificial Intelligence (AI), AI-based content creation, digital marketing, and personal branding. This activity demonstrates that Canva-based digital content design training can be an effective tool to support the sustainable development of the younger generation's digital competencies.